RANCANG BANGUN APLIKAIS PEMESANAN AIR GALON PADA DEPOT WINDY BERBASIS ANDROID - Laia, Darman Hati; Silalahi, Mesri (Computer Science and Industrial Engineering, 2023)
ABSTRACT Water is one of the primary needs in human life, starting from daily activities such as drinking, bathing, cooking, to the field of industrial processing on a large scale, therefore good quality water is needed. Depot Windy is a refill drinking water business produced by PT. Lautan Bening which has been operating since 2016, with daily sales of around 200-300 gallons issued from 07.00 AM - 19.00 PM. However, there are problems related to the distribution of information between administrators, delivery staff and customers, so unwanted things often occur, such as gallons being stolen, gallons not being picked up, and payment transactions being delayed. In this journal, the author describes the development of an android-based gallon water ordering application using the SDLC (Software Development Life Cycles) method and the Waterfall development method which is connected via the user's cellphone. By creating good communication facilities, it can make it easier for sellers and customers to make transactions online and in real time, make it easier for customers to know the availability of gallons of water, and achieve the company's long-term goal of increasing sales.